The Differentiated Instruction and Its Implementation for Developing Countries: Partnership Students Learning Indonesian Language in Bridging Course Program - Nuning Catur Sri Wilujeng (JOURNAL OF EDUCATION, 2012)
Students are unique human beings. They are not always alike. As they have  different  backgrounds, interests, cultures, and learning dynamics, they learn differently. The Developing Countries Partnership students in YSU, Indo nesia come from different countries with different levels of Indonesian language competences. In order to get the reflection of students' personal  best learning style and the degree of individual progress from each learner s achievements, some steps need to be applied in differentiated instructions. While teachers need to facilitate and coach students in learning, this  instruction will enable the students to actively participate in learning, producing, and assessing their own learning. The result shows there is only one fully autonomous student; two semi autonomous students, one introvert who does not like working in group, and one extrovert; and three other dependent students who always need Google translation to help them in doing their tasks.   Keywords:  different learner, differentiated instruction